Oxygen Hyperbaric Exposure Induces GLUT4 Expression Reduction and No Folliculogenesis Alterations in Rat PCOS with Insulin Resistance Model - Varianida Veterini; Budi Santoso; Widjiati Widjiati (Majalah Obstetri dan Ginekologi, 2015)
Objectives: To know effect of hyperbaric oxygen therapy to GLUT4 expression and folliculogenesis in rat PCOS with insulin resistent model.Materials and Methods: this is an analytic experimental study used 30 rats induced by testosterone propionate injection 1 mg/100 g body weight daily for 28 consecutive days as a PCOS with insulin resistent model. Animal models divided into 3 groups. Negative control was not given treatment, positive control was given placebo. Treatment group was given hyperbaric oxygen 2.4 ATA 90 minutes 2x5 days. GLUT4 expression determined by immunohystochemistry to m. Gastrocnemius. Hematoxylin Eosin staining to rat ovaries were performed to know differentiation in folliculogenesis. The results were then compared.Results: There were significant decrease of GLUT4 expression in treatment group (mean0,84+0,47)compared to negative and positive control (mean3,96+3,16and3,36+2,17). There were no different folliculogenesis in these groups.Conclusion: Hyperbaric oxygen 2.4 ATA 90 minutes 2x5 days induce decrease of GLUT4 expression and no alterations in folliculogenesis in rat PCOS with insulin resistent model, therefore can not yet be used as alternative therapy in PCOS.